Impact of stressors in the aviation environment on xenobiotic dosimetry in humans: physiologically based prediction of the effect of +Gz-forces. Issue 10 (18th May 2020) - Sweeney, Lisa M.
ABSTRACT: The application of physiologically based modeling approaches in evaluating health risks in diverse environments is limited by scarcity of comprehensive reviews detailing how physiological parameters are altered due to stressors. A modern high-performance aviation environment in particular has the potential for simultaneous exposure to chemical and non-chemical stressors which may interact via non-chemical stressor-mediated pharmacokinetic alterations. To support physiologically based pharmacokinetic (PBPK) modeling of in-flight disposition inhaled chemicals, literature review, and synthesis was conducted to determine the impact of gravitational (+Gz) forces on PBPK modeling inputs. Specifically, changes in cardiac output and related parameters heart rate and stroke volume, breathing frequency, tidal volume, and pulmonary and alveolar ventilation rate in vivo were extracted from 36 publications and related mathematically to +Gz intensity. A scenario was simulated where a pilot performing test flights might inhale organic chemicals at the occupational exposure guideline level while experiencing sustained, elevated +Gz. Peak arterial blood concentrations of 1, 2, 4-trimethylbenzene during a 1 h-flight at +4 Gz were predicted to increase 2-fold relative to would occur on the ground under baseline conditions. This case study demonstrates the potential value of scenario-specific physiological information in assessing changes in risk-relevant internal dosimetry, providing better information for potential risk management actions.